Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I should get sum of the following minimums.Is there any way to solve it?

$$\min\left\{2,\frac{n}2\right\} + \min\left\{3,\frac{n}2\right\} + \min\left\{4,\frac{n}2\right\} + \cdots + \min\left\{n+1, \frac{n}2\right\}=\sum_{i=1}^n \min(i+1,n/2)$$

share|improve this question
1  
Just split the summation in two halves ($i+1 \leq n/2$ and $i+1 > n/2$) and evaluate both sums seperately. –  TMM Sep 30 '11 at 21:11
    
I was wondering if the question is to prove the identity mentioned in the question. The word "solve" is abused! :-) –  Srivatsan Sep 30 '11 at 21:16
add comment

2 Answers 2

up vote 1 down vote accepted

Suppose first that $n$ is even, say $n=2m$. Then $$\min\left\{i,\frac{n}2\right\}=\min\{i,m\}=\begin{cases}i,&\text{if }i\le m\\ m,&\text{if }i\ge m. \end{cases}$$

Thus, $$\begin{align*} \sum_{i=2}^{n+1}\min\left\{i,\frac{n}2\right\} &= \sum_{i=2}^m i + \sum_{i=m+1}^{n+1} m\\ &= \frac{m(m+1)}2-1 + (n+1-m)m\\ &= \frac12\left(\frac{n}2\right)\left(\frac{n}2+1\right)-1+\left(\frac{n}2\right)\left(\frac{n}2+1\right)\\ &= \frac{3n(n+2)}{8}-1\\ &=\frac{3n^2+6n-8}8. \end{align*}$$

If $n$ is odd, say $n=2m+1$, $$\min\left\{i,\frac{n}2\right\}=\min\left\{i,m+\frac12\right\}=\begin{cases}i,&\text{if }i\le m\\ m+\frac12,&\text{if }i> m. \end{cases}$$

Thus, $$\begin{align*} \sum_{i=2}^{n+1}\min\left\{i,\frac{n}2\right\} &= \sum_{i=2}^m i + \sum_{i=m+1}^{n+1} \left(m+\frac12\right)\\ &= \frac{m(m+1)}2-1 + (n+1-m)\left(m+\frac12\right)\\ &= \frac12\left(\frac{n-1}2\right)\left(\frac{n+1}2\right)-1+\left(\frac{n}2\right)\left(\frac{n+3}2\right)\\ &= \frac{3n^2+6n-1}{8}-1\\ &= \frac38 (n^2+2n-3). \end{align*}$$

share|improve this answer
    
Since you've solved it completely: one could unify the even and odd cases as $\frac{3n^2}{8}+\frac{3n}{4}-1-\frac{1-(-1)^n}{16}$ for $n > 1$. The "odd formula" is zero when $n=1$, while the sum evaluates to $\frac12$. –  J. M. Sep 30 '11 at 21:54
add comment

If $n$ is even, your sum splits as

$$\sum_{i=1}^{\frac{n}{2}-2} \min\left(i+1,\frac{n}{2}\right)+\frac{n}{2}+\sum_{i=\frac{n}{2}}^{n} \min\left(i+1,\frac{n}{2}\right)=\sum_{i=1}^{\frac{n}{2}-2} (i+1)+\frac{n}{2}+\frac{n}{2}\sum_{i=\frac{n}{2}}^{n} 1$$

If $n$ is odd, you can perform a similar split:

$$\sum_{i=1}^{\frac{n-3}{2}} (i+1)+\frac{n}{2}\sum_{i=\frac{n-1}{2}}^{n} 1$$

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.